Faktor Peyebab Stres Residen Dalam Menjalani Rehabilitasi Pemulihan Adiksi NAPZA di Yayasan GEMA (Generasi Emas Aceh) - Dian Fanika Sari dian; Wirda Amalia (JAROW: Journal of Ar-Raniry on Social Work, 2023)
Rehabilitation is a place of recovery for drug addiction victims, but during recovery, residents experience stress & difficulty in controlling their stress. The stress felt by residents is different, namely some do not like being locked up and are bored, so if it is not addressed it will have a negative impact on recovery, those who cannot manage stress well may be less effective in recovering every day. Based on these findings, researchers tried to find a solution to this problem by coping with stress. This research aims to determine the factors that cause stress. This research uses descriptive qualitative methods. The sample in this study was 6 residents who participated in rehabilitation, sampling used a saturated sampling technique. Data collection techniques used were observation, interviews, documentation. Based on the results of the data analysis, it can be concluded that the most influential factors causing resident stress are being pensive a lot, not accepting being rehabilitated, excessive boredom resulting in the emergence of negative thoughts outside the Foundation, these negative thoughts can hinder the resident from undergoing recovery sincerely and arise because Residents are less comfortable and not enthusiastic about undergoing the program so they cannot adjust and are not good at adapting.